Bringing Some Clarity to Role Ambiguity Research - Pearce, Jone L. (Academy of Management Review, 1981)
Theoretical development of the concept of role ambiguity and empirical research on this concept have proceeded fairly independently of one another. Empirical work has confounded role ambiguity with both job dissatisfaction and formalization. A new model of ambiguity is offered, emphasizing unpredictability, rather than information deficiency. This model accords with expectancy theory.